Student nurse perceptions : a case study to illuminate the perceptions developed by student nurses which result in absenteeism as the behaviour of choice in response to difficulties in their educational programme - Heighway, Valerie (School of Education, 2016)
The problem which prompted the undertaking of this study was that of increasing absenteeism amongst student nurses at one South African Nursing College. The information, obtained from individual and group interviews, was analysed to identify the perceptions developed by student nurses. Absenteeism is shown to be a behavioural response to environmental and other factors in the world of the student nurse. A theoretical model is proposed to explain three main types of absenteeism and the factors which contribute to absenteeism and attendance.